Doping Group IIB Metal Ions into Quantum Dot Shells via the One‐Pot Decomposition of Metal‐Dithiocarbamates. Issue 5 (24th February 2015) - Bear, Joseph C.; Hollingsworth, Nathan; Roffey, Anna; McNaughter, Paul D.; Mayes, Andrew G.; Macdonald, Thomas J.; Nann, Thomas; Ng, Wing H.; Kenyon, Anthony J.; Hogarth, Graeme; Parkin, Ivan P.
<x xml:space="preserve">Abstract</x> Almost half of solar energy reaching the Earth is in the infrared, and for solar cells, IR absorbing/emitting quantum dots are highly effective photovoltaic materials. As a possible approach to generating such materials, an investigation into the incorporation of group IIB metal ions during the shelling of II–VI and III–V semiconductor core/shell quantum dots is presented. Quantum dot shells consist of ZnS and an additional metal sulphide, obtained from the decomposition of metal dithiocarbamate single‐source precursors. Resultant quantum dots are characterized and interrogated using transmission electron microscopy, high‐resolution transmission electron microscopy, electron diffraction, time‐of‐flight‐secondary ion mass spectroscopy, X‐ray photoelectron spectroscopy, energy dispersive X‐ray spectroscopy, photoluminescence emission and lifetime spectroscopy, and UV–vis spectroscopy. It is demonstrated that on incorporation of an additional metal sulphide during shelling, photoluminescence properties change dramatically according to the element and indeed, its concentration. Tunable infrared emission is achieved for Hg addition, thus a one‐pot method for the synthesis of infrared emitting quantum dots from visible luminescent cores is hereby developed.